MAPPING LITHOLOGICAL AND MINERALOGICAL UNITS USING HYPERSPECTRAL IMAGERY - Thannoun, Rayan Ghazi (Malaysian Journal of Science, 2021)
Hyperspectral images such as the Earth Observer-1 (EO-1) provides an efficient method of mapping surface mineralogy because it can measures the energy in narrower bands compared with multispectral sensors. The Kirkuk anticline northern Iraq is one of the most petroleum-rich provinces. It is characterized, that is an asymmetrical, cylindrical anticline, with a fold axis trend towards North West- East, South East. The study’s primary goal is to apply satellite processing and techniques on the Eo-1 imagery for identifying lithological and mineral units at a part of Kirkuk anticline northern Iraq. The EO-1 image was corrected at the beginning of atmospheric impacts using the FLAASH module in ENVI software. Processing of (Minimum Noise Fraction- MNF) processing was applied and then it reduced the dimensionality of data, as well as, the processing of (PPI) pixel purity index was applied to spatial reduction. This study tested the potential of (spectral angle mapper supervised classification-SAM) classification for mapping the lithological and mineral units using the Hyperion imagery. three different sources of endmembers or spectra are used for SAM classifications. The one: is done by Analytical Spectral Devices (ASD) Spectrometer. The second: reference spectra have been taken from the spectral library of USGS. Third: extracting endmembers from the purest pixels of the hyperion image, which was done by applying (MNF and PPI). The endmembers were provided, generated as the training area for SAM classification. The present results demonstrated the great potential of data used to map the distribution of alteration of minerals and lithological units in a part of Kirkuk anticline. The classified Hyperion image shows that Jarosite and illite are the most dominant altered minerals, as well as, the main lithological units of the upper member of Fatha formation are revealed in the core of the Kirkuk anticline with scattered and small outcrops towards the flanks.